Síntesis, caracterización de c-aquil y c-fenil-pirogalol[4]arenos funcionalizados con grupos carboxilo en el borde superior y evaluación de su interacción con cationes orgánicos de interés biológico (2020)
In this research work, our attention was focused on synthesis, characterization, and study of the molecular interaction of C-alkyl and C-phenyl-pyrogallol[4]arenes with three important biological important organic cations known as neurotransmitters. In this sense, the polyphenolic macrocycles tetra(propyl)-pyrogallol[4]arene, tetra(phenyl)-pyrogallol[4]arene and tetra(4-hidroxyphenyl)-pyrogallol[4]arene were synthesized using butanal, benzaldehyde, and 4-hidroxybenzaldehyde respectively in reaction with pyrogallol in ethanol as solvent in all cases, afterward, the isomers mixture was characterized employing spectroscopic methods (1H-NMR, 13C-RMN, 2D-NMR, and FT-IR) and mass spectrometry(ESI-MS) and, a methodology was developed that allows an efficient separation of each isomer. The three macrocycles were derivatized on the upper rim with acetyl and benzoyl groups employing acetic anhydride and benzoyl chloride achieved a total functionalization of each isomer. Finally, the molecular interaction between the neurotransmitters choline, betaine and carnitine with the macrocycles functionalized and without functionalization in cone and boat conformation was carried out in gas phase and solution. The interaction studies indicated that the macrocycles functionalized form 1:1 complexes host-guest with the three neurotransmitters in the gas phase, while the macrocycles without functionalized, only the tetra(propyl)-pyrogallol[4]arene formed complexes with the neurotransmitters. The noncovalent interactions studies in solution indicated that the cone and boat conformers are affective hosts for the three neurotransmitters and some hosts with potential applications in host-guest systems and supramolecular assemblies.